Penggunaan Absensi Digital dalam Meningkatkan Disiplin Pegawai (Studi Kasus Dinas Pendidikan Kabupaten Purwakarta) - Emmalia Emmalia; Ujang Abdul Fatah; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
Digital transformation in the government sector has become an urgent need to improve the quality of governance and performance of civil servants. One form of implementation is the use of a digital attendance system as a replacement for the conventional attendance recording system. This study aims to identify and analyze the implementation process, obstacles, and impact of the use of digital attendance on improving employee work discipline at the Purwakarta Regency Education Office. The approach used is a case study. Data collection methods include passive participatory observation, in-depth interviews, and documentation studies. Data analysis uses the Miles, Huberman, and Saldana model and the Planning, Organizing, Actuating, and Controlling (POAC) management function approach from George R. Terry. The results of the study indicate that (1) The implementation of digital attendance based on facial recognition and GPS-based applications has significantly changed employee attendance patterns; (2) This system is able to present accurate, real-time attendance data, and is free from manipulation, thus encouraging increased punctuality and compliance with work regulations; (3) Although technical obstacles were found in the form of networks and differences in technological adaptability, the system's linkage with the Employee Performance Allowance (TPP) and consistent supervisory policies make this system run effectively. In conclusion, the implementation of a digital attendance system based on facial recognition and GPS in the Purwakarta Regency Education Office has been implemented in accordance with applicable regulations, and has been able to significantly increase the level of employee discipline.